UNDERSTANDING THE PERFORMANCE IN TRAVEL AGENCIES, A LITERATURE REVIEW APPROACH - Fitri, Diin (Journal of Management and Leadership, 2024)
Organizational performance is one of the main factors in determining organizational success. Previous research used several dimensions to measure performance. There are three organizational performance results, namely financial performance, product market results and shareholder return. Many measurements can be used in calculating performance measures. This is due to the influence of different stakeholders and the needs of each organization. In this research the author takes a different perspective by analyzing organizational performance through the travel agency industry. It's just that this research focuses on travel agents in Spain. That's why this research aims to find out more about measuring travel agency performance.